CODE-SWITCHING IN MULTILINGUAL ROVING PEOPLE’S CONVERSATIONS - Bramantoko, Beda; Ardi, Priyatno (Sanata Dharma University, 2023)
This paper aims at analyzing the types of code-switching in the conversation of multilingual roving people, who move from one country to another country. The participants of this qualitative research were five multilingual roving people. Audio recordings and interviews were used to collect the data. The results reveal that the types of code-switching employed by the multilingual roving people were intra-sentential switching, inter-sentential switching, situational switching, and metaphorical switching. The researchers also found that the factors influencing the multilingual roving people in switching the codes included the speaker, interlocutors, changes in the situation because of the third person, and changes in the topic. The researchers concluded that the type of code-switching that appeared the most was intra-sentential switching and the most influencing factor why the participants did code-switching was the interlocutors.